2020
DOI: 10.1371/journal.pgen.1008750
|View full text |Cite
|
Sign up to set email alerts
|

ArdC, a ssDNA-binding protein with a metalloprotease domain, overpasses the recipient hsdRMS restriction system broadening conjugation host range

Abstract: Plasmids, when transferred by conjugation in natural environments, must overpass restriction-modification systems of the recipient cell. We demonstrate that protein ArdC, encoded by broad host range plasmid R388, was required for conjugation from Escherichia coli to Pseudomonas putida. Expression of ardC was required in the recipient cells, but not in the donor cells. Besides, ardC was not required for conjugation if the hsdRMS system was deleted in P. putida recipient cells. ardC was also required if the hsdR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…ardA -H1 expression as dsDNA. Some anti-restriction genes, such as the E. coli ardC gene, are expressed in the recipient strain as dsDNA; also, the protein is not exported from the donor to the recipient cells, as demonstrated by González-Montes et al 2020 [ 17 ]. Therefore, this mechanism may increase gene acquisition in the bacterial hosts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ardA -H1 expression as dsDNA. Some anti-restriction genes, such as the E. coli ardC gene, are expressed in the recipient strain as dsDNA; also, the protein is not exported from the donor to the recipient cells, as demonstrated by González-Montes et al 2020 [ 17 ]. Therefore, this mechanism may increase gene acquisition in the bacterial hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this mechanism may increase gene acquisition in the bacterial hosts. Those authors also suggested that inhibition of ArdC activity could provide a new tool to hinder the transmission of multidrug resistance [ 17 ]. However, other authors have hypothesized that ardA could be transcribed from single-stranded (conjugative) DNA (ssDNA), prior to the synthesis of complementary DNA in the recipient strain, possibly due to the presence of specific secondary structures formed by ssDNA [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, based on their role in the conversion of ss to dsDNA and/or inhibition of host-encoded defence mechanism, it is clear that the establishment genes play a crucial role in the conjugation process, and hence should be considered as part of the conjugation module, together with the genes in the large conjugation operon. This conclusion is supported by the demonstrated importance of ard genes in the establishment of conjugative plasmids in the new host [36][37][38][39]. Therefore, most genes present on the pLS20 family plasmids are related to the conjugation process, e.g., 69 of the 92 genes (75%) of pLS20 form part of the conjugation module.…”
Section: Establishment Regulons Present On Pls20 Family Of Plasmids and Implications Of Establishment Regulons In Generalmentioning
confidence: 90%
“…Phages and plasmids may defeat host restriction-modification (RM) systems with anti-restriction proteins, which frequently block type I DNA RM enzymes ( e.g. , Zavilgelsky and Rastorguev 2009 ; Serfiotis-Mitsa et al 2010 ; Balabanov et al 2012 ; Roberts et al 2012 ; Piya et al 2017 ; González-Montes et al 2020 ). Low-specificity DNA modification enzymes expressed only for the entering molecule are also found in prophages ( Murray et al 2018 ) and plasmids ( Fomenkov et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%